ANALISIS FAKTOR PENENTU KINERJA PEGAWAI PADA KANTOR DINAS PERHUBUNGAN KABUPATEN MIMIKA(Kantor Dinas Perhubungan Kabupaten Mimika) - Abdul Rahim; Habel Taime (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to determine the factors that influence the performance of employees at the Mimika Regency Transportation Office. This study uses a descriptive method of data collection through questionnaires sourced from employees at the Mimika Regency Transportation Office, with a sample size of 57 respondents. Data analysis was conducted using Confirmatory Factor Analysis (CFA) with the assistance of SPSS version 26. The results of the analysis revealed that out of the four factors (leadership style, supervision, work discipline, and work motivation) that determine employee performance at the Mimika Regency Transportation Office, all indicators were found to align with their respective factors. Among these four factors, the most significant factor in determining employee performance at the Mimika Regency Transportation Office was found to be the supervision factor.